Pengaruh Pendapatan Wajib Pajak, Kualitas Pelayanan, dan Pemahaman Literasi Perpajakan terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan di Kelurahan Keboledan Kecamatan Wanasari Kabupaten Brebes Periode Tahun 2021-2023 - Siti Adelah Sofiyati; Dumadi Dumadi; Hilda Kumala Wauandari (Jurnal Visi Manajemen, 2024)
Tax revenue from this sector is not small, so the government must optimize its services and also be able to provide stimulus to the community so that they are willing to pay taxes, because with the high tax revenue from this sector, financing for regional development will be able to be carried out properly. This research aims to determine the influence of taxpayer income, service quality and understanding of tax literacy in Keboledan Village. This research is with a quantitative descriptive approach. Data analysis technique with multiple linear regression analysis. The population in this study is all taxpayers in Keboledan Village of 2.39 people. The sampling technique in this study used the Slovin formula with a margin of error of 5% obtained by 343 respondents. The results of this study obtained a t-value of 4,115>1,967 and a significance value of 0.000<0.05, which means that taxpayer income has a positive and significant effect on the compliance of land and building tax taxpayers in Keboledan Village. The quality of service has a t calculation of 4,434>1,967 and a significance value of 0.000<0.05 which means that the quality of service has a positive and significant effect on the compliance of land and building taxpayers in Keboledan Village. The understanding of tax literacy has a t count of 8,131>1,967 and a significance value of 0.000<0.05 which means that the understanding of tax literacy has a positive and significant effect on the compliance of land and building taxpayers in Keboledan Village. It is believed that taxpayer income, service quality and tax literacy understanding together affect land and building tax compliance in Keboledan Village.